Framing the education for gifted Lebanese and gifted refugees in Lebanon - Antoun, Maya (Frontiers in Psychology, 2022)
The paper provides a comprehensive conceptual model or framework for the identification and programming of gifted education in Lebanon. The model is evidence-based on the critical review of the literature on gifted education over the past two decades. The model discussed topics related to teacher conceptions, identification, preparation, and practices for the gifted in Lebanon. The development of a culturally appropriate conceptual model of gifted education is locally focused on Lebanese teachers’ needs to identify and serve gifted Lebanese and gifted refugee learners. This framework provides a means for educational leaders in Lebanon to consider policy reforms that will benefit not only gifted learners but also gifted refugee learners in different educational settings.